Millimeter-wave receiver concepts for 77 GHz automotive radar in silicon-germanium technology - Kissinger, Dietmar (SpringerBriefs in Electrical and Computer Engineering, 2012)
The book presents the analysis and design of integrated automotive radar receivers in Silicon-Germanium technology, for use in complex multi-channel radar transceiver front-ends in the 77GHz frequency band. The main emphasis of the work is the realization of high-linearity and low-power modular receiver channels as well as the investigation of millimeter-wave integrated test concepts for the receiver front-end.